2009
DOI: 10.3208/sandf.49.525
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Bearing Capacity of Piles in Liquefiable Soils

Abstract: An investigation into the base capacity of piles in passing through loose, liqueˆable sand and founded in underlying dense sand is presented based on the results of a series of dynamic centrifuge tests on instrumented model pile groups. Excess pore pressures equal in magnitude to the initial eŠective vertical stress were observed to be generated in the bearing layer of dense sand at both shallow (15 m) and deep (26 m) depths. This induced a dramatic reduction in base capacity and consequently, large settlement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Equations ( 13) and ( 15) have been widely used in bridge engineering design in China, considering the influence of factors such as velocity and sediment movement at the bottom of the river bed on the erosion depth, and have the advantage of high stability of the calculation results [27]. However, the left and right dimensions are not uniform, the calculation is more complicated, and there are many related parameters that need engineering experience to evaluate.…”
Section: Local Scour Calculationmentioning
confidence: 99%
“…Equations ( 13) and ( 15) have been widely used in bridge engineering design in China, considering the influence of factors such as velocity and sediment movement at the bottom of the river bed on the erosion depth, and have the advantage of high stability of the calculation results [27]. However, the left and right dimensions are not uniform, the calculation is more complicated, and there are many related parameters that need engineering experience to evaluate.…”
Section: Local Scour Calculationmentioning
confidence: 99%
“…During reconsolidation, any settlement at the tip affects the development of drag load. Knappett and Madabhushi (2009) used load measurements from a series of centrifuge tests on piles in liquefiable soils and proposed an empirical model [Eq. ( 2)] to estimate the ultimate pile tip capacity in liquefying soil (q r u t;ult ) as a nonlinear function of the free-field excess pore pressure ratio (r u ) at a depth of the pile's tip…”
Section: Qzliq Materials Propertiesmentioning
confidence: 99%
“…where q o t;ult = ultimate tip capacity when r u ¼ 0; and the α t = material constant, which, according to the empirical model of Knappett and Madabhushi (2009), only depends on the effective friction angle (ϕ 0 ) of the soil at the tip. Sinha (2022) performed several centrifuge tests on axially loaded piles in liquefiable soils and found a very good agreement with the previously proposed model [as defined in Eq.…”
Section: Qzliq Materials Propertiesmentioning
confidence: 99%
“…Coelho et al (2004) performed dynamic centrifuge tests on uniform deposits of saturated sands and showed that the mechanisms of excess pore pressure generation and liquefaction are similar in dense and loose sand, with the rate of excess pore pressure generation being slower in dense sand. Centrifuge tests of pile groups by Knappett and Madabhushi (2009) and Madabhushi (2010, 2013) observed substantial settlements of piles during shaking when the excess pore pressures were high around the shaft and near the tip. After shaking, as soil reconsolidated and drag load developed, the resulting settlement in the piles was much smaller.…”
Section: Introductionmentioning
confidence: 99%